Limited Nomination Reliability Using Single‐ and Multiple‐item Measures. Issue 3 (11th September 2013) - Babcock, Ben; Marks, Peter E. L.; Crick, Nicki R.; Cillessen, Antonius H. N.
Abstract This article examines a variety of reliability issues as related to limited nomination sociometric measures. Peer nomination data were collected from 77 sixth grade classrooms. Results showed that, although some single‐item peer nomination measures were relatively reliable, many single‐item peer nomination measures using limited nominations were quite unreliable. Overt aggression nomination items were the only set of single‐item measures where mean classroom reliability estimates were .75 or greater. Combining multiple items led to substantially better reliability, as combining the two least reliable items for a category into a single measure made the composite more reliable than the most reliable single measure. Having more nominators in the sample also increased reliability. The limited nomination items overall tended to be less reliable than similar unlimited nomination items from other studies. The authors end with recommendations for obtaining the most reliable peer nomination data possible from a study.